Ingestion of an Amino Acid Electrolyte Beverage during Resistance Exercise Does Not Impact Fluid Shifts into Muscle or Performance - JohnEric W. Smith; Ben M. Krings; Timothy J. Peterson; Jaden A. Rountree; Roksana B. Zak; Matthew J. McAllister (MDPI AG, 2017)
The purpose of this study was to investigate the impact of ingesting an amino acid-electrolyte (AAE) beverage during upper body resistance exercise on transient muscle hypertrophy, exercise performance, markers of muscle damage, and recovery. Participants (n = 15) performed three sets of six repetitions-bench press, lat pull down, incline press, and seated row-followed by three sets of eight repetitions at 75% of the estimated 1 repetition maximum-triceps kickback, hammer curl, triceps push down, and preacher curl-with 90 s of rest between sets. The final set of the push down/preacher curl was performed to failure. Prior to and immediately post-exercise, as well as 24, 48, and 72 h post exercise, cross-sectional muscle thickness was measured. Blood samples were collected prior to exercise, as well as 24, 48, and 72 h post-exercise for serum creatine kinase (CK) analysis. No treatment effect was found for muscle cross-sectional area, repetitions to failure, or serum CK. A main effect (p < 0.001) was observed in the change in serum CK levels in the days following the resistance exercise session. The findings of this study suggest that the acute ingestion of a AAE beverage does not alter acute muscle thickness, performance, perceived soreness and weakness, or markers of muscle damage.